Analisis Kualitas Pelayanan Laboratorium Komputer Dell Politeknik Industri Furnitur Dan Pengolahan Kayu - Niki Etruly; Safarah Putri Ma wa (Jurnal Ekonomika dan Bisnis, 2023)
The Dell Computer Laboratory is located at the Polytechnic of Furniture and Wood Processing Industry which is a form of service to students' knowledge and skills in the field of digital drawing, especially for students in the Furniture Design study program. Dell Computer Laboratory is one of the laboratories with the busiest schedule in each semester because it is always used as a practicum room for Furniture Design students. Therefore, researchers believe it is necessary to analyze and find out the level of customer satisfaction with the quality of services that have been provided in order to provide input to laboratory management, in improving the quality of services provided as the level of customer satisfaction is better in the future. The variables used in this study are tangible, responsiveness, assurance, empathy, and reliability. These variables are processed using multiple linear regression to determine whether it partially and simultaneously have a significant effect on service satisfaction. From the results of data processing and discussion, it is found that the tangible variable has no relationship with service satisfaction because the t-count value is negative. The responsiveness variable has a relationship with service satisfaction because the t-count value is 0.501 but it is not significant because the t-count value is smaller than the t-table of 0.68. Assurance, empathy, and reliability variables have a significant relationship with service satisfaction because they have positive t-count values ​​and they are greater than the t-table with values ​​of 0.985, 2.873, and 1.600, respectively.